PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS III SD NEGERI 157 PEKANBARU - Siti Zahroh (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
Based on the observation and experience during the researcher at SD Negeri 157 Pekanbaru, there weresymptoms especially in Civics lesson as follows: 1) out of 32 students, only a small number were able to scoreabove the minimum criteria, 2) lack of students' curiosity of the lessons conveyed by teachers in the classroom,this is known from at least students who want to ask or propose his opinion. This classroom action research wasconducted in third class at SD Negeri 157 Pekanbaru. The time of this study is planned for 1 month ie inFebruary 2016. The form of this research is collaborative class action research. Collaborative research in thisresearch involves one person as an observer. In this research observer is a teacher of class III SD Negeri 157Pekanbaru. Based on the results of analysis and discussion as presented in chapter IV can be concluded thatwith the use of demonstration methods can improve learning outcomes on subjects of Civics in students of classIII SD Negeri 157 Pekanbaru. This success is due to during the demonstration the teacher should give thestudents a chance to observe well and ask about the difficulties faced by the students. In the end the student seeksa movement or perhaps an answer with his own effort based on the correct facts, as well as lessen errors whencompared with just reading or explaining, because students get a clear picture of the results of his observations.